2023
DOI: 10.3390/ijms24119777
|View full text |Cite
|
Sign up to set email alerts
|

Zooming into Gut Dysbiosis in Parkinson’s Disease: New Insights from Functional Mapping

Abstract: Gut dysbiosis has been involved in the pathogenesis and progression of Parkinson’s disease (PD), but the mechanisms through which gut microbiota (GM) exerts its influences deserve further study. Recently, we proposed a two-hit mouse model of PD in which ceftriaxone (CFX)-induced dysbiosis amplifies the neurodegenerative phenotype generated by striatal 6-hydroxydopamine (6-OHDA) injection in mice. Low GM diversity and the depletion of key gut colonizers and butyrate producers were the main signatures of GM alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…However, this finding can be as a result of an as yet not understood therapeutic threshold for butyrate being exceeded which causes the normally beneficial SCFA to become, in fact, detrimental as demonstrated in vitro (Huang et al, 2014). One study that does replicate observations in humans is that of Turco et al (Turco et al, 2023). It was found that the combination of antibiotic induced dysbiosis in the 6-hydroxydopamine model of PD resulted in not only a more severe onset of PD like symptoms but also a reduction in butyrate in the stool of the animals (Turco et al, 2023).…”
Section: Butyrate In Preclinical Models Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this finding can be as a result of an as yet not understood therapeutic threshold for butyrate being exceeded which causes the normally beneficial SCFA to become, in fact, detrimental as demonstrated in vitro (Huang et al, 2014). One study that does replicate observations in humans is that of Turco et al (Turco et al, 2023). It was found that the combination of antibiotic induced dysbiosis in the 6-hydroxydopamine model of PD resulted in not only a more severe onset of PD like symptoms but also a reduction in butyrate in the stool of the animals (Turco et al, 2023).…”
Section: Butyrate In Preclinical Models Of Pdmentioning
confidence: 99%
“…One study that does replicate observations in humans is that of Turco et al (Turco et al, 2023). It was found that the combination of antibiotic induced dysbiosis in the 6-hydroxydopamine model of PD resulted in not only a more severe onset of PD like symptoms but also a reduction in butyrate in the stool of the animals (Turco et al, 2023). It is therefore unclear how these findings implicate butyrate in preclinical models of PD and more investigation is warranted.…”
Section: Butyrate In Preclinical Models Of Pdmentioning
confidence: 99%